The book as a symbol in library design in the digital age - Gallo-León, José-Pablo (Anuario ThinkEPI, 2022)
Library design is no longer centered on the storage of books. Libraries are designed around people and their needs. However, it seems that the physical book continues to be widely used in a representative way, even precluding the use for which it was intended. The book is used as an iconographic symbol that shows that a building is a library. This symbolic function seems to stem from the need to highlight a building´s status as a library. Thus, its librariness is assured thanks to a symbol rather than its function, but this is not necessarily a bad thing.